1995
DOI: 10.1002/crat.2170300805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonics on Agglomeration

Abstract: Crystal size distribution of potassium aluminium sulphate dodekahydrate prepared under various conditions has been used for characterization of the degree of agglomeration of crystals. Six series of batch precipitation experiments with batch times from 2 to 80 minutes have been represented by a) dried crystals, b) the same crystals partially de-agglomerated before the measurement, c) wet crystals taken directly from the batch, d) the same crystals partially de-agglomerated before the measurement, e) wet crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This is attributed to the fact that the reaction between Ca 2+ and CO 3 2– is significantly enhanced by ultrasonic irradiation, leading to the formation of loose scale floccules suspending in the solution, which can be easily washed away by the flowing liquid. This finding of accelerating reaction is consistent with Nishida et al, but different from what is reported in some literatures, , i.e., a retardation effect on the crystallization of calcium carbonate is introduced with ultrasonic irradiation, the induction time is prolonged and the ionic reaction is retarded to obstruct the formation of scale…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This is attributed to the fact that the reaction between Ca 2+ and CO 3 2– is significantly enhanced by ultrasonic irradiation, leading to the formation of loose scale floccules suspending in the solution, which can be easily washed away by the flowing liquid. This finding of accelerating reaction is consistent with Nishida et al, but different from what is reported in some literatures, , i.e., a retardation effect on the crystallization of calcium carbonate is introduced with ultrasonic irradiation, the induction time is prolonged and the ionic reaction is retarded to obstruct the formation of scale…”
Section: Resultssupporting
confidence: 86%
“…In addition, ultrasonic irradiation shows superior characteristics, including cost-effectiveness, longevity, and environmental friendliness, as compared to chemical treatment methods. , It is difficult to determine the antiscaling efficiency and dissolution capacity for a specific scale in an oilfield, because there usually exists more than one type of scale. ,, No attempts have been made to systematically and quantitatively examine effects of frequency and acoustic intensity on the antiscaling efficiency. So far, contradictory statements on how ultrasonic irradiation affects crystallization have been found in the literature: accelerating reaction and retarding reaction. , Ultrasonic irradiation is found to significantly accelerate the reaction of Ca 2+ and CO 3 2– ions together with a shortened crystallization initiation time. On the contrary, it is deemed to be difficult for these two ions to react and form scale under ultrasonic irradiation due to the retarded crystal growth rate through dehydration and surface diffusion, imposing no effect on either the morphology or size of the formed calcium carbonate. , Such contradictory findings might be explained by considering different experimental conditions. As for the accelerating reaction, the ultrasonic frequencies used in the experiments are 24 kHz, whereas retarding reaction is found in a highly supersaturated solution with the ultrasonic irradiation of 17.7 Hz …”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been widely reported to influence the primary nucleation process accelerating nucleation kinetics, this is typically expressed in terms of reducing the induction time and MSZW [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Ultrasound can also increase the rate of secondary nucleation, this is manifested as a reduction on the product crystal size distribution [20,22,24,31,32,[34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the technique of ultrasound irradiation has been used in the preparation of different functional materials during their precipitation from solution. Thus, it has been reported that ultrasonic irradiation can accelerate or retard precipitation , change the crystal size distribution and shape of crystals , or cause agglomeration of particles of different materials. Several authors have been investigating the effect of ultrasound application on the precipitation of calcium carbonate , particularly on its crystal growth , particle size , aggregation , and scaling .…”
Section: Introductionmentioning
confidence: 99%